(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores methods of learning English using artificial intelligence. The current age of modern technology cannot be imagined without the external factor of digitalization and parallel with the emergence of the educational environment thanks to various innovations that are especially brought by the OpenAI organization. All this significantly expands the acquisition of a foreign language and even introduces pleasant innovations, namely, it increases the percentage of interest of young people in learning English and allows them to feel greater freedom in the process of learning new material. The use of modern services provided from this side is a significant step towards the professional development of youth. It not only improves language skills, but also promotes the development of critical thinking, creativity and independence. Taken together, the use of artificial intelligence in teaching English opens up new horizons and opportunities, making the educational process more productive and enjoyable.